A four decades multiparametric investigation in a Mediterranean dynamic ecosystem: Mollusc assemblages answer to the environmental changes. (5th March 2020) - Leonardi, M.; Bergamasco, A.; Giacobbe, S.; Azzaro, F.; Cosentino, A.; Crupi, A.; Lanza, S.; Randazzo, G.; Crisafi, E.
Abstract: The ecosystem changes of "Marinello coastal lakes" - a brackish dynamic area located on the Tyrrhenian coast of Sicily (Italy) - have been examined through the analysis of the adaptive response of mollusc assemblages to the geomorphological and environmental changes. In particular, we have contextually analysed the changes in salinity, mud and organic carbon together with mollusc abundance and distribution, comparing the data sets from several multidisciplinary investigations that we performed in about forty years. Our studies have evidenced that the space-time dynamics of the geomorphological, environmental and trophic parameters have led the progression of Marinello ecosystem, favoring the onset of transient windows of connectivity (TWCs) between different habitats. TWCs, by supporting continuous re-arrangements of mollusc populations, have contributed to increase the functional and ecological complexity of the system. Salinity in particular has proven to be the most affecting factor on the diversification of mollusc assemblages, explaining 63% and 44% of variation for brackish and marine species respectively. In addition, the distribution of both detritus and suspension feeders has been mostly affected by salinity. The interannual analysis of the mollusc assemblages has shown in the whole system a generalised increase in the number of species, likewise, also the species richness recorded in each basin generally increased with the time. Metapopulations in the Marinello ecosystem have shown to be related to significant modifications in the habitat patches, in turn connected to the anthropogenic interventions or to the geomorphological progression of the entire physiographic system. Significant relationships among biotic and abiotic parameters have highlighted important implications on the ecosystem functioning, suggesting their possible application in the improvement of investigation tools for the transitional environments. Highlights: Marked changes in geomorphological, environmental and trophic parameters have driven the decadal dynamics of the Marinello brackish ecosystem. Adaptive answers of mollusc assemblages closely follow ecosystem changes. Detritus and suspension feeders tracked salinity changes. Transient Windows of Connectivity (TWCs) among fragmented habitats promote equalizing mechanisms of coexistence between mollusc populations. Early and late successional stages simultaneously coexist and quickly evolve, increasing the functional and ecological complexity.